Crowd‐sourced reporting of birds nesting on power lines in Iran. (15th August 2022) - Kolnegari, Mahmood; Hazrati, Mandana; Tehrani, Vahid Khodaei; Dwyer, James F.
Abstract: Birds frequently nest on overhead electrical infrastructure, which can lead to electrocutions, equipment damage, fires, and power outages when birds or nests contact energized equipment. Consequently, it is important that electric utilities have data‐driven plans for addressing avian nesting on power structures. Iran's Birds and Power Lines Committee (IBPLC) establishes guidelines for how electric utilities in Iran address avian interactions with electrical infrastructure. To support the IBPLC, we gathered information on avian nesting on power lines in Iran by searching posts from 4 crowd‐sourced groups: Bargh News, the Iranian linemen group on Instagram, and the Power Distribution Lines Experts and Linemen of Iran groups on Telegram. Contributions (e.g., postings) for each of these groups was limited to electric utility personnel in Iran. We reviewed photos and contacted members in the groups to identify nesting species and voltages of the electrical infrastructure supporting nests. We found 976 nests reported by 89 linemen from January 2019 through December 2020. Most (88%) were found during routine operations and maintenance, but some (12%) were found during power outage investigations. Most (77%) were on distribution pylons, with the rest (23%) on transmission towers. Of the nests found, 203 (21%) were species protected under Iranian law due to small and declining populations. The information we gathered was used by IBPLC to revise electric utility guidelines and ban the destruction of occupied nests (containing eggs or young) on power structures, except in cases where nests create an immediate safety hazard to nesting birds, electric utility linemen, or the public. Abstract : We gathered crowd‐sourced data from electric utility‐focused social media user groups to identify bird species, line voltages, and nest locations for birds nesting on power lines in Iran. Users reported nearly 1000 nests over two years. These data facilitated revision of management recommendations to reduce impacts to avian populations while simultaneously improving electric reliability.